A novel design method for 3D elliptical vibration-assisted cutting mechanism. (April 2019) - Zhang, Chen; Song, Yun
Highlights: A novel design method for elliptical vibration-assisted cutting mechanism is proposed and the basic design flowchart based on the actual design requirements and the output elliptical locus is established in the paper. A simplified motion schematic of EVC mechanism is designed by considering the layout form of input displacement axis and the structural schematic of EVC mechanism is constructed by establishing the relationship between subchain form and the detailed structural form. The kinematic model of the pseudo-rigid-body EVC mechanism is theoretically established to verify the correctness of structure design based on the structural schematic. Based on the proposed design method, a 3D elliptical vibration-assisted cutting mechanism is established and the output performance of the established 3D elliptical vibration-assisted cutting mechanism is optimized by discrete method with combining the FEM. Abstract: The elliptical vibration-assisted cutting (EVC) mechanism is an important unit in the EVC process. However, most of structural designs of EVC mechanism are customized, and these design cannot be applied in other EVC mechanism. This can be contributed to that no general design principle is refined from these actual designs and result in low design efficiency. A novel design method for 3D EVC mechanism is proposed in the paper. First, a simplified motion schematic is designed by considering the layout form of input displacement axis, which can be used to generate 3D motion in space. Then the structural schematic is constructed by considering the relationship between subchain form and the detailed structural form. Based on the designed schematic, the model of EVC mechanism is established and the kinematic model is theoretically analyzed. Finally, FEM is used to analyze and optimize the established EVC mechanism. In order to verify the feasibility of the proposed method, a design case based on the actual requirements is given. The actual 3D EVC device is fabricated and its 3D elliptical loci is verified. The design case indicates that the proposed method for the EVC mechanism is satisfactory and can be applied in other designs.